Measuring young adult appeal for menthol and non-menthol cigarettes: protocol of a clinical trial using both laboratory and intensive longitudinal methods (PRISM). Issue 4 (28th April 2022) - Cohn, Amy M; Pickworth, Wallace; Audrain-McGovern, Janet; Murphy, James; Villanti, Andrea C; Hedeker, Donald; Dunn, Delaney; Wyatt, Riley; Niznik, Taylor; Cotten, Whitney; Smith, Michael; Ehlke, Sarah J
Abstract : Introduction: Although the Food and Drug Administration banned other characterising flavours in cigarettes, menthol cigarettes are still available to consumers. Young adult new smokers are initiating with menthol cigarettes, such that the prevalence of young adults menthol versus non-menthol smokers is increasing. Experimentation with menthol cigarettes is associated with progression to regular smoking and nicotine dependence. This ongoing clinical trial in young adult smokers measures appeal and the reinforcing value of smoking menthol versus non-menthol cigarettes and the impact of these variables on changes in smoking behaviour at a 6-month follow-up. Methods and analysis: Reinforcement for menthol smoking is assessed in the laboratory using a validated behavioural economic choice task, and appeal is measured in the natural environment using ecological momentary assessment (EMA). Analyses will examine differences between menthol and non-menthol cigarette smoking on measures of subjective response in the laboratory and via EMA, and how subjective response mediates the association between menthol preference at baseline and smoking outcomes at follow-up. Ethics and dissemination: This protocol was approved by the University of Oklahoma Health Sciences Center Institutional Review Board (#10581). The findings will isolate the unique effects of menthol in smoking and will help inform regulatory decisions about the abuse liability of menthol cigarettes. Findings will be disseminated through peer-reviewed journal articles and presentations at national and international conferences. Trial registration number: NCT03953508 .